Tugas Pemimpin Muda Kristen Masa Kini Sebagai Gembala Menurut 1 Timotius 4 - Santy Sahartian; Samuel Brian Septiadi (Angelion, 2020)
Abstract: The church is God's people who need guidance and leadership so that people can know God. Therefore the Church needs a leader who understands his duties as a leader. But there are still church leaders who do not understand their duties as leaders based on Bible principles. The church is less prepared for the younger generation as leaders. This we can see in the church in general does not provide opportunities for young people to develop their potential to lead. This church's disbelief in youth leadership is increasingly apparent because of the life of the Christian youth itself. Aside from not being able to be considered capable, the church is reluctant to entrust great responsibility to the youth because the lives of Christian youth are often considered far from God's word. Today's young Christian leaders are those who carry out Christian leadership duties at a relatively young age. Today's young leaders have so many weaknesses that young leaders are less accepted and respected by many people, so that Christian youths are trusted they must carry out the duties of young Christian leaders today according to 1 Timothy 4 namely young Christian leaders should remind the congregation of the word, teach the truth of the word , be an example for God's people who are led, grow in service, supervise themselves and teachings. So that the Christian Young leaders can be respected by everyone.Keywords: Task, Young Leaders, I Timothy 4Abstrak: Gereja merupakan umat Allah  yang memerlukan pembinaan dan kepemimpinan sehingga umat dapat mengenal Allah. Maka dari itu Gereja membutuhkan sosok pemimpin yang memahami tugasnya sebagai pemimpin. Namun masih ditemukan pemimpin gereja yang kurang memahami tugasnya sebagai pemimpin berdasarkan prinsip-prinsip Alkitab. Gereja kurang mempersiapkan generasi muda sebagai pemimpin. Hal ini dapat kita lihat di dalam gereja secara umum tidak memberikan kesempatan bagi pemuda untuk mengembangkan potensinya dalam memimpin. Ketidak pecayaan gereja terhadap kepemimpinan pemuda ini semakin nyata karena kehidupan pemuda Kristen itu sendiri. Selain karena kurang di anggap mampu, gereja enggan mempercayakan tanggung jawab yang besar kepada pemuda karena kehidupan pemuda Kristen yang sering kali dianggap jauh dari firman Tuhan.  Pemimpin muda Kristen masa kini adalah seorang yang menjalankan tugas kepemimpinan Kristen dalam usia yang relative muda. Pemimpin muda masa kini memiliki banyak sekali kelemahan sehingga pemimpin muda kurang diterima dan dihargai oleh orang banyak, agar pemuda kristen dipercayai maka harus menjalankan tugas pemimpin muda Kristen masa kini t menurut 1 Timotius 4 yaitu  pemimpin muda kristen seharusnya mengingatkan jemaat akan firman, mengajarkan kebenaran firman, menjadi teladan bagi umat Tuhan yang dipimpin, bertumbuh dalam pelayanan, mengawasi diri dan ajaran. Sehingga pemimpin Muda Kristen dapat dihargai seiap orang.Kata- kata kunci: Tugas, Pemimpin Muda, I Timotius 4